Level Of Knowledge And Behavior Preventive For Surgical Site Infections Among Nurses In Indonesia: A Cross-Sectional Correlational Study - Janwar Olang; Michael Ramos Pangaribuan; Mareta Cecilia; Oktaviani Simamora; Mega Sampepadang (Universitas Pahlawan Tuanku Tambusai, 2026)
Surgical Site Infections (SSIs) are serious postoperative complications that increase the risk of morbidity, mortality, and healthcare costs. Nurses play a crucial role in preventing SSIs, particularly in inpatient wards. Data from 2024 recorded an SSI incidence rate of 0.18%, highlighting the need to improve adherence to prevention protocols. This study aimed to examine the relationship between nurses’ knowledge and practices in preventing SSIs. A descriptive correlational design with a cross-sectional approach was used. A total of 96 nurses were selected through total sampling. Data were collected using valid and reliable questionnaires and analysed using univariate and bivariate methods, including the Spearman test. Results showed that 30.2% of nurses had good knowledge, 68.75% had moderate knowledge, and 1% had poor knowledge. Additionally, 52.1% demonstrated positive practices, while 47.91% demonstrated negative practices. The analysis shows that the Spearman correlation coefficient (ρ) between knowledge level and preventive behaviour is 0.235, indicating a positive but weak relationship. This suggests that higher levels of knowledge are generally associated with better SSI prevention behaviour, although the strength of this association is limited. The p-value (p = 0.021) is below the significance threshold of α = 0.05, demonstrating that the relationship is statistically significant. It is recommended that hospitals enhance training, education, and supervision to improve compliance with SSI prevention protocols.